Interdisciplinary research and teaching-training endeavours in Croatia. The Upper Ravni Kotari region case. - Černelić, Milana; Rajković Iveta, Marijeta (2008)
Research and teaching-training is organised as part of the teaching programms of the Department of Ethnology and Cultural Anthropology on the Faculty of Humanties and Social sciences in Zagreb (course: Teaching Research Practices) for several years. Its aim is to organize fieldwork education for the students. In 2004. it became the part of research programme „ Mostovi“ (the Bridges), which was created as the synergy of interdisciplinary research and the application of its results to the local conditions of the the Upper Ravni Kotari region. The activities are therefore focused on two connected levels: - to research the potential of the traditional way of living as well as contemporaneous needs and aspirations of local people - to design an institutional framework for practical initiatives in local dayly life (connected with the Stojan Jankovic Castle as an integral eco/cultural monument complex and foundation of the Center for Interculturalism and Sustainable Development). The region is populated with both Croat Roman Catholic and Serb Orthodox population and the communication between them was heavily disturbed during Croatian war of independence. Our paper will deal with presentation of the activities of the students of ethnology and cultural anthropology within this programme.. The research was carried out in November 2005. and in April 2006, when also the students of history participated in it. Students of other disciplines are also planned to be included in the project in future, as well as the students from other European countries. After the fieldwork is done the students are educated how to work on the collected materias (transcribing conversations, comparing them, analysing and sinthesizing them, preparing them for publication). The aim of such research and teaching-training for students is to gain skills how to get experience in field research and use its results for sustainable development. It is innovative in a way that students are prepared to apply the gained skills both in research and practical work in nearby future, for example, in eco-museums, participating in cultural and rural tourism and so on. In this way the teaching-training is focused on students capacities for their future work.
Projekt MZOS
ENG